Comparison of Lignolytic Bacteria in Sago Pith, Wet Sago Four, and Sago Hampas - Tenriawaru, Eka Pratiwi; Hamdani, Ulfah Zakiyah; Rahmawati, Hilda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Lignin is a component of crude fiber found in sago stems and is difficult to degrade. The aim is to compare lignolytic bacteria in sago pith, wet sago flour, and sago hampas in three (3) layers of waste piles. Samples were obtained from a traditional sago factory in Palopo City. Lignolytic bacteria were isolated using an M9 minimum agar supplemented with 1% lignin. The research parameters were the total lignolytic bacteria and the number of different colonies in each sample. The results showed that the most lignolytic bacteria and different colonies were found in the sago pith and the least in the middle layer of the sago hampas pile. The research results conclude that the sago pith can be an alternative source of lignolytic bacterial isolates. However, the ability of these lignolytic bacteria still needs to be tested and selected to obtain potential isolates.